Dravet syndrome associated with cortical dysplasia of Taylor-type - Wright, Rosemary; Hernandez, Angel; Malik, Saleem; Donahue, David J.; Alles, Ajit; Perry, M. Scott (Journal of Pediatric Neurology, 2011)
Severe myoclonic epilepsy of infancy or Dravet syndrome is a catastrophic epilepsy of genetic origin that begins with febrile seizures in the first year of life and evolves to intractable epilepsy with cognitive decline and frequent episodes of status epilepticus. While multiple treatment strategies are employed, rarely are patients with Dravet syndrome considered for resective epilepsy surgery. We report a case of Dravet syndrome in which palliative resection of epileptogenic foci revealed cortical dysplasia of Taylor-type. We discuss the association of cortical dysplasia with Dravet syndrome and consider the utility of palliative surgical therapy in a genetically based epilepsy syndrome.
Keywords: Dravet syndrome; severe myoclonic epilepsy of infancy; epilepsy surgery; cortical dysplasia